When a Subsidiary Loses its Status: Towards an Identification-based Model of Host Country Nationals' Willingness to Share Knowledge with Expatriates - Yamao, Sachiko (Institutional Knowledge at Singapore Management University, 2013)
We theorize how a foreign subsidiary’s loss of its status relative to other units of the same multinational corporation (MNC) will influence host country national (HCN) managers’ dual organizational identification and their willingness to share knowledge with expatriate managers. In particular, we examine the two contingent scenarios of subsidiary status loss (i.e., the parent-driven and subsidiary-engaged) that may lead HCN managers to develop different organizational identification (i.e., MNC-oriented and subsidiary-oriented). We then propose that different organizational identification of HCN managers will lead them to develop varying levels of willingness to share knowledge with expatriates. We further propose that HCN managers’ generalized identification with expatriate managers moderates the relationship between HCN managers’ organizational identification and their willingness to share knowledge with expatriates.